2016
DOI: 10.1093/mmy/myw070
|View full text |Cite
|
Sign up to set email alerts
|

In Vitroactivity of Manuka Honey and polyhexamethylene biguanide on filamentous fungi and toxicity to human cell lines

Abstract: Soft-tissue invasive fungal infections are increasingly recognized as significant entities directly contributing to morbidity and mortality. They complicate clinical care, requiring aggressive surgical debridement and systemic antifungal therapy. To evaluate new topical approaches to therapy, we examined the antifungal activity and cytotoxicity of Manuka Honey (MH) and polyhexamethylene biguanide (PHMB). The activities of multiple concentrations of MH (40%, 60%, 80%) and PHMB (0.01%, 0.04%, 0.1%) against 13 cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 62 publications
(44 reference statements)
4
20
0
Order By: Relevance
“…Concentrations in the region of 40% (w/v) could be achievable; however, efficacy at this concentration needs to be experimentally tested. This potentially brings its own challenges as manuka honey can exert in vitro toxicity on human cells (Yabes et al, 2017). The differences between EVPL bronchiole tissue in the presence of 64% (w/v) manuka honey may be subject to these similar “ in vitro” effects, however, the negative effects observed in vitro do not necessarily occur in vivo whereby 100% manuka honey is used on open wounds with positive effects, increasing wound healing (Mohamed et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Concentrations in the region of 40% (w/v) could be achievable; however, efficacy at this concentration needs to be experimentally tested. This potentially brings its own challenges as manuka honey can exert in vitro toxicity on human cells (Yabes et al, 2017). The differences between EVPL bronchiole tissue in the presence of 64% (w/v) manuka honey may be subject to these similar “ in vitro” effects, however, the negative effects observed in vitro do not necessarily occur in vivo whereby 100% manuka honey is used on open wounds with positive effects, increasing wound healing (Mohamed et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In an in vitro cytotoxicity test using cultured human skin fibroblasts, PHMB was extremely cytotoxic and appeared to induce complete cell destruction in the majority of cells 112 . When used in vitro at or below concentrations commonly employed in human wound care, PHMB (0.01%, 0.04%, and 0.1%) demonstrated both time‐ and concentration‐dependent cytotoxicity in cultured human keratinocytes and osteoblasts, but only time‐dependent cytotoxicity in cultured fibroblasts 113 . Furthermore, exposure of cultured human endothelial cells to PHMB (0.0006%‐0.01%) resulted in a large reduction in cell number and viability 125 .…”
Section: Resultsmentioning
confidence: 98%
“…109 Studies have shown different levels of cytotoxicity among PVP-I, PHMB, and silver-containing products (Table 2). [110][111][112][113][114][115][116][117][118][119][120][121][122][123][124][125][126][127][128][129] Cytotoxicity data, in particular data derived from in vitro studies, must be interpreted with caution as any cytotoxic effects observed in cultured cell types can be magnified and may not be truly reflective of the in vivo or clinical setting. 49,130,131…”
Section: Cytotoxicity and Tolerabilitymentioning
confidence: 99%
“…Honey or honey-resistance mechanisms might therefore also have downstream effects for biofilm formation or the expression of other virulence factors. On the other hand, because honey has shown effective inhibition of a wide range of pathogens (Carter et al, 2016;Hillitt et al, 2017;Yabes et al, 2017), and the principal genes involved in honey resistance in our experiment are conserved in multiple pathogenic species (e.g., nemR or analogues are present in Klebsiella pneumonia, Acinetobacter baumannii and Salmonella typhimurium), our work identifies candidate loci that may be involved in resistance in other species. This is another relevant area for future research in the context of medical honey application.…”
Section: %mentioning
confidence: 98%